Stakeholders' perception on blockchain technology in Indian aviation industry: a focus group study. (30th September 2022) - Damodaran, Akhil; Kumar, Rupesh; Bangwal, Deepak; Khanka, Sheetal; Shree, Deep
Blockchain is a new emerging technology, and its implementation in the field of aviation is very recent. The study has taken the case of Indian airports where its implementation is under progress. The experts were invited to understand their perception of blockchain implementation in the Indian aviation industry. The study helps to understand the practical issues that management goes through when they are implementing the blockchain system in Indian aviation sector. With the help of using focus group, the study identified stakeholder perceptions on blockchain implementation in the Indian aviation industry. The significant themes that emerged from the discussion are stakeholder consultation, regulation, manpower, security privacy, and infrastructure. Thus, the study has some critical managerial implications for the identified factors.